Tom Clancy duty and honor [compact disc, unabridged] - Blackwood, Grant; Clancy, Tom, 1947-2013 (A Jack Ryan, Jr. novel, 2016)
Written with Grant Blackwood, this is the twentieth book in the Jack Ryan Jr. series. Follow Jack Ryan Jr. on another suspenseful journey fighting corruption and finding answers.